证明:用二项式定理展开+均值不等式.
因为(a-1)(b-1)=ab-(a+b)+1=1,得ab=(a+b)>=2(ab)^(1/2),得ab>=4.(当仅当a=b=2取等号a,b>0)
又2^n=(1+1)^n=C(n,0)+C(n,1)+...+C(n,n-2)+C(n,n-1)+C(n,n),
得C(n,1)+...+C(n,n-2)+C(n,n-1)=2^n-C(n,0)-C(n,n)=2^n-2
而
(a+b)^n=C(n,0)b^n+C(n,1)ab^(n-1)+C(n,2)a^2b^(n-2)+...+C(n,n-2)a^(n-2)b^2+C(n,n-1)a^(n-1)b+C(n,n)a^n,倒序有
(a+b)^n=C(n,n)a^n+C(n,n-1)a^(n-1)b+C(n,n-2)a^(n-2)b^2+...+C(n,2)a^2b^(n-2)+C(n,1)ab^(n-1)+C(n,0)b^n
注意到C(n,i)=C(n,n-i),0==2*2^n*[2^n-2],(当仅当a^ib^(n-i)=a^(n-i)b^i及a=b=2取等号)所以有(a+b)^n>=(a^n+b^n)+(2^n)*(2^n-2),
即(a+b)^n-(a^n+b^n)>=2^(2n)-2^(n+1),命题得证.